Trigonometric Approximation in Reflexive Orlicz Spaces (Analysis in Theory and Applications, 2011)
The Lipschitz classes $Lip(α,M)$, $0 < α ≤1$ are defined for Orlicz space generated by the Young function $M$, and the degree of approximation by matrix transforms of $f \in Lip(α,M)$ is estimated by $n^{−α}$.